Overcoming the rise in local deposit resistance during electrophoretic deposition via suspension replenishing - Tiwari, Prabal; Ferson, Noah D.; Arnold, David P.; Andrew, Jennifer S. (Frontiers in Chemistry, 2022)
Nanomaterials have unique properties, functionalities, and excellent performance, nanomaterials and as a result have gained significant interest across disciplines and industries. However, currently, there is a lack of techniques that can assemble as-synthesized nanomaterials in a scalable manner. Electrophoretic deposition (EPD) is a promising method for the scalable assembly of colloidally stable nanomaterials into thick films and arrays. In EPD, an electric field is used to assemble charged colloidal particles onto an oppositely charged substrate. However, in constant voltage EPD the deposition rate decreases with increasing deposition time, which has been attributed in part to the fact that the electric field in the suspension decreases with time. This decreasing electric field has been attributed to two probable causes, (i) increased resistance of the particle film and/or (ii) the growth of an ion-depletion region at the substrate. Here, to increase EPD yield and scalability we sought to distinguish between these two effects and found that the growth of the ion-depletion region plays the most significant role in the increase of the deposit resistance. Here, we also demonstrate a method to maintain constant deposit resistance in EPD by periodic replenishing of suspension, thereby improving EPD’s scalability.